2021
DOI: 10.1109/access.2020.3046671
|View full text |Cite
|
Sign up to set email alerts
|

Power Flow Calculation of Distribution Network With Multiple Energy Routers

Abstract: Energy router is an emerging device based on power electronic technology, which can realize the flexible distribution of electric energy in the power system. Therefore, the use of energy routers to improve the operating conditions of the power system not only has broad development prospects, but also brings economic benefits. In this regard, this paper proposes a steady-state model of a single energy router and considers the loss of the DC/DC transformer, establishes a power flow equation with multiple energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…When f i > f g , the individual sparrows are vulnerable to attacks by predators, and when f i = f g , the sparrows approach other sparrows to reduce their chances of being preyed upon. Initialise the population size N , ratios of predators r pr and scouts r sc , warning value WV , and maximum iteration number t max 2: Generate the improved logistic population according to Equation (7) 3: Calculate the initial fitness, current optimal fitness and worst fitness of the sparrow population position…”
Section: Fusion Of a Laplacian Distribution And An Inverse Incomplete...mentioning
confidence: 99%
See 1 more Smart Citation
“…When f i > f g , the individual sparrows are vulnerable to attacks by predators, and when f i = f g , the sparrows approach other sparrows to reduce their chances of being preyed upon. Initialise the population size N , ratios of predators r pr and scouts r sc , warning value WV , and maximum iteration number t max 2: Generate the improved logistic population according to Equation (7) 3: Calculate the initial fitness, current optimal fitness and worst fitness of the sparrow population position…”
Section: Fusion Of a Laplacian Distribution And An Inverse Incomplete...mentioning
confidence: 99%
“…Energy routers are regarded as the primary network units for implementing energy internet [3–5]; therefore, energy routers are expected to become core components of future microgrids and 5G BS power supply systems [6]. Previous research [7] has demonstrated the advantages of energy routers with a focus on traditional power grids, which cannot meet the needs of microgrids involving multiple distributed energy sources. In another work [8], the authors proposed flexible scheduling of the microgrid through the energy router, and an algorithm was used to achieve maximum benefit from the overall microgrid system.…”
Section: Introductionmentioning
confidence: 99%
“…In the first stage, a preliminary topology structure is obtained by allocating reliability indices to cope with potential DG output and load changes. In the second stage, scheme is carried out using the CC&G algorithm to maximize the reliability of the system In addition, due to the special properties of the distribution network, its optimization model has non convex and nonlinear characteristics, thus increasing great computational complexity [16]- [17]. Heuristic algorithms can automatically search for the optimal solution, thereby improving the efficiency and accuracy of distribution network reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…Galvanically DC/DC isolated converters [5] are employed to provide voltage adaptation and a similar behavior as AC transformers. A lot of development has been done around DCTs: new topologies with modular designs [6], development of high power bulk power processing converters with high power semiconductor switches [7], multiport converters [8,9] and energy routers [10][11][12]. Converters can be controlled in closed-loop, typically with topologies such as Dual Active Bridge (DAB) [13], or in open-loop, using resonant topologies.…”
Section: Introductionmentioning
confidence: 99%